DAMPAK PROGRAM PLBK (PENATAAN LINGKUNGAN BERBASIS KOMUNITAS) YANG DIDUKUNG OLEH UNIT PENGELOLA KEUANGAN PNPM MANDIRI TERHADAP PERILAKU MASYARAKAT DAN TINGKAT KESEJAHTERAANNYA - Ardiansyah, Muhammad Awaluddin (Jurnal Ekonomi & Studi Pembangunan, 2016)
This study aims to determine the effect of Community-Based Neighborhood Arrangement (PLBK) program from PNPM Mandiri to the behavior and welfare level of the community in Kecamatan Lalabata, Soppeng regency of South Sulawesi. This PLBK program includes the establishment of government schools, the construction of hospitals and the provision of the Financial Management Unit (UPK). This research uses mixed methods method. Quantitative methods use simple linear regression analysis while qualitative methods use in-depth interviews with Leiden Ethnosystems. The results of this study indicate that the most influential variable in increasing the economic level of the community is the interest rate provided by the UPK. While in the program of behavior change and changes in the level of community welfare, the establishment of free schools and the construction of hospitals is expected to encourage people to improve their education level and quality of health. The results of this study indicate that the function of IMM (Integrated Microfinance Management) is a solution to the problem of poverty and in rural communities.